Professional learning in a school-based community of science teachers - Melville, Wayne Stuart (Curtin University, 2005)
This thesis investigates professional learning in a school-based community of science teachers. Transcripts of science staff meetings were analysed using two frameworks. These frameworks relate to the notions of community and professional learning. The school-based community is interpreted in terms of three metaphors of understanding: meanings, practice and identity. Professional learning is interpreted in terms of how the teachers learn the episteme, techne and phronesis of their science teaching. I propose that professional learning occurs when teachers engage in virtues-based personal reflection and/or public discourse around episteme, techne and phronesis in the spaces 'in-between' the metaphors of community. This proposition raises implications for the accessibility of professional learning and the relationship between community and organisational boundaries.